Design Innovation and Validation of a Non-Electric Hearing Aid for Improved Usability - Kiat Ng, Poh; Siong Jee, Kian; Wah Thong, Li; Ai Yeow, Jian (International Journal of Engineering and Technology, 2018)
This study aims to innovate and validate the design of a non-electric hearing aid for improved usability. Studies on conventional and existing hearing aids were carried out before the actual study on developing this non-electric hearing aid was done. The final product underwent a series of evaluations in order to verify its viability and usability. Conceptualisation, material selections and concept selections were carried out in order to select the most appropriate concept for this study. The material selection process ensures that the choice of material is appropriate for the specific requirements of the components to be achieved. Subsequently, a detailed cost analysis was carried out to ensure that the manufactured product would be affordable to the customers. Several experiments and tests were performed to evaluate the productâ€™s performance. Although a validated prototype for a non-electric hearing aid is in hand, future improvements on the fabricated product are still needed in order to ready the product for its future commercialisation phase.Â